AÇÕES AFIRMATIVAS DO PODER PÚBLICO COMO INSTRUMENTO DE INCLUSÃO SOCIAL: UMA ANÁLISE DA LEI DE Nº 12.990/2014 E DA AÇÃO DECLARATÓRIA DE CONSTITUCIONALIDADE, N.º 41 - Carvalho, Germano Pontes; França, Mhardoqueu Geraldo Lima (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Racism in Brazil is structural. To combat it, it is necessary that the Government propose affirmative actions to promote economic and social equality for the insertion of the black population in society. These affirmative actions are forms of public policies that aim to promote well-being and citizenship to ensure equal opportunities and treatment among people and the mobilization of cultural sectors with the intention of expanding social inclusion actions. The Dignity of the Human Person is a fundamental right inscribed in the Brazilian Federal Constitution, inserted in article 1, item III. The objective of this paper was to discuss the principle of the dignity of the human person as a legal good protected by the Federal Constitution in the crimes of racism in Brazil. To this end, historical and social aspects will be addressed, as well as the effectiveness of these affirmative public policies that aim to promote the insertion of the black population in society.